ANALISA PROFESIONALISME SERVICE ATTENDENT PADA DIVISI FOOD AND BEVERAGE SERVICE DI HOTEL PARAI CITY GARDEN SIJUNJUNG - Vina Kumala (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Hotel is a form of commercially managed accommodation, providing for guests to obtain lodging services in the form of food and drinks. The professionalism of service attendants at Parai City Garden Sijunjung Hotel still needs to be improved with various problems that usually occur during peak sessions. Service standards at Parai City Garden Sijunjung Hotel need to be improved in terms of being friendly, fast and precise. The method used for research is to use descriptive qualitative research, which explains that qualitative research is intended as a type of research whose findings are not obtained through statistical procedures or other forms of calculation but rather collect data through interviews and observations of two techniques commonly associated with qualitative methods. The efforts to improve service attendent performance for guest services are through training that is held regularly once a month, mastering product knowledge, awarding the best employees every three months and once a year, and making comparisons with other better hotels. At peak sesion service attendent prepare everything that will be used by guests to eat, restaurants that serve and provide enough food for the guests of the group then the most important coordination with the kitchen as a food provider, the division of tasks appropriately act according to orders from the captain or food and baverange.Keywords: Hotel, Professionalism of service attendant/waitress, peak season